Komposisi Dan Dominasi Patotipe Xanthomonas oryzae pv. oryzae Penyebab Hawar Daun Bakteri Pada Tanaman Padi Dengan Pola Tanam Tidak Serempak - Yuliani, Dini; Sudir, Sudir (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2017)
Research to determine the dynamics of composition and domination of Xanthomonas oryzae pv. oryzae (Xoo) pathotype, the bacterial leaf blight (BLB) pathogen of rice in areas with different planting time was carried out in Klaten Regency, Central Java Province, in the Wet Season (WS) 2014/2015 and Dry Season (DS) 2015. The research consisted three steps, namely: observation and sampling of plants in the field, isolation the pathogen in the laboratory, and pathotype identification in the greenhouse. Observations and samplings of diseased plants in each growing season were conducted at planting time, i.e.: early planting (I), mid planting (II), and late planting (III). The results showed that Xoo pathotype composition in WS 2014/2015 and DS 2015 were pathotype III, IV, and VIII with varying dominance between the planting period in the season, as well as between seasons, and between observation location. The composition of Xoo pathotype was dominated by pathotype IV in the early and mid planting periods of WS 2014/2015, whereas at the end of planting period was dominated by pathotype III. Xoo composition in early, mid, and late planting periods of DS 2015 was dominated by pathotype III. Based on these results is suggested to control BLB in non synchronous cropping pattern at early and mid planting period of wet season by planting resistant varieties to Xoo pathotype IV, while in areas the late planting period, it is suggested to planting resistant varieties to Xoo pathotype III and VIII. The BLB control in areas with early, mid, and late planting periods of dry season is suggested to planting resistant varieties to Xoo pathotype III or VIII.